Penterjemahan kata kerja bahasa Mandarin kepada bahasa Melayu: (shuo 'berkata') (Jurnal Bahasa, 2022)
This article studies the word-equivalence of Mandarin verb, (shuo 'to say') in Malay as found in an antholqgy of short stories translated from the Mandarin original texts. The anthology is entitled Cerpen Pilihan Sastera Manhua III: Dalam Hujan Renyai (Selected Literary Short Stories Manhua III: During a Drizzle). The article aims at studying the appropriateness of word-equivalence selection in Malay by six different translators in the anthology. A total of ten Mandarin words and their respective word-equivalences in Malay were studied, but for the purpose of this paper only the case of the Mandarin verb iR (shuo 'to say') and its Malay equivalences were reported in some detail here. Nonetheless, the implication it had on the remaining nine Mandarin verbs and their respective equivalences were also mentioned. It was found that there were multiple word-equivalences in Malay for the one Mandarin verb (shuo 'to say'). Among the obvious consequences of such a phenomenon in the translation works under study were the existence of various types of translation output such as appropriate (correct) translation, over translation, undertranslation and incorrect translation. The word equivalences that gave accurate translation far surpassed those giving inaccurate ones. On the whole it was the contextual meaning of the verb that essentially determined the selection of the appropriate word-equivalence in Malay.